4a-12=2a+6

Simple and best practice solution for 4a-12=2a+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4a-12=2a+6 equation:


Simplifying
4a + -12 = 2a + 6

Reorder the terms:
-12 + 4a = 2a + 6

Reorder the terms:
-12 + 4a = 6 + 2a

Solving
-12 + 4a = 6 + 2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2a' to each side of the equation.
-12 + 4a + -2a = 6 + 2a + -2a

Combine like terms: 4a + -2a = 2a
-12 + 2a = 6 + 2a + -2a

Combine like terms: 2a + -2a = 0
-12 + 2a = 6 + 0
-12 + 2a = 6

Add '12' to each side of the equation.
-12 + 12 + 2a = 6 + 12

Combine like terms: -12 + 12 = 0
0 + 2a = 6 + 12
2a = 6 + 12

Combine like terms: 6 + 12 = 18
2a = 18

Divide each side by '2'.
a = 9

Simplifying
a = 9

See similar equations:

| 1-3x^2-4x^3=0 | | 470+2x=330+4x | | 18x+27y=10 | | -7(3x+6)+x=-6x-4(6x+8) | | 7(x+10)=140 | | x/2-8.5=15 | | f(x)=-6+3x | | 3x-7=72 | | (x+2)-(-3x-8)= | | 24x^2+20x-24= | | -16+2d=5+4d | | 3x^2-265=3x^2-10x+6.25 | | -8d+18-9+15d= | | 2+3(t+7)=6t-2+2t | | .7g-4=10 | | -2=10-2.5x | | 8v-4v=144-64 | | 11-14b+10= | | s(t)=-16t^2+50t+4 | | .03m-1.2=-.48 | | 9(d+4)-8=5d | | 12-6d=-27 | | y=-10x-7 | | 5(2x-4)=4x+10 | | 19y+4y= | | s(t)=16t^2+50t+4 | | -4=3x+y | | .5w-10=.75w | | -25x-3=5x-7 | | 10+7r+15r-3= | | 20x-60=2x-60 | | 4x+35x=180 |

Equations solver categories